2021
DOI: 10.3390/math9131467
|View full text |Cite
|
Sign up to set email alerts
|

Differential Games for an Infinite 2-Systems of Differential Equations

Abstract: A pursuit differential game described by an infinite system of 2-systems is studied in Hilbert space l2. Geometric constraints are imposed on control parameters of pursuer and evader. The purpose of pursuer is to bring the state of the system to the origin of the Hilbert space l2 and the evader tries to prevent this. Differential game is completed if the state of the system reaches the origin of l2. The problem is to find a guaranteed pursuit and evasion times. We give an equation for the guaranteed pursuit ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Khalifa and Kumar [21] investigated cooperative continuous static games in a crisp environment, defining and determining the first-kind stability set corresponding to the solution without differentiability. Under uncertainty environment, some recent researchers for cooperative games have been introduced (Mallozzi and Messalli [22], Bigdeli and Hassanpour [23], Elshafei [24], Zaichenko [25], Zidan et al [26], Donahue et al [27], Ganzfried [28], Zhou et al [29], Krishankumar et al [30,31], Tukhtasinov et al [32], Sivagami et al [33], Zhao et al [34], Megahed [35], Romanuke [36], and Khalifa et al [37]).…”
Section: Introductionmentioning
confidence: 99%
“…Khalifa and Kumar [21] investigated cooperative continuous static games in a crisp environment, defining and determining the first-kind stability set corresponding to the solution without differentiability. Under uncertainty environment, some recent researchers for cooperative games have been introduced (Mallozzi and Messalli [22], Bigdeli and Hassanpour [23], Elshafei [24], Zaichenko [25], Zidan et al [26], Donahue et al [27], Ganzfried [28], Zhou et al [29], Krishankumar et al [30,31], Tukhtasinov et al [32], Sivagami et al [33], Zhao et al [34], Megahed [35], Romanuke [36], and Khalifa et al [37]).…”
Section: Introductionmentioning
confidence: 99%
“…For an infinite system of binary differential equations in the space l 2 , we have studied an evasion differential game problem. In [42], it has been shown that if the pursuer control set contains the evader control set, i.e., if ρ > σ, then the pursuit can be completed for a finite time. Consequently, if in game (3) ρ k > σ for some k ∈ {1, 2, .…”
Section: Discussionmentioning
confidence: 99%
“…For an infinite system of binary differential equations in the Hilbert space l 2 , the pursuit differential game of one pursuer and one evader was studied in [42], when the pursuer's control set contains the evader's control set.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to show that u 0 is admissible, i.e., there exists τ > 0 such that ∥u 0 ∥ ≤ ρ. For any x 0 ∈ ℓ 2 with ∥x 0 ∥ 2 2 ≤ κ 2 ρ 2 , then (17) implies that x(τ) = 0 for the solution started from x 0 . The definition of W(τ) (12) and (15)…”
Section: Proof Of Theorem 2 Definementioning
confidence: 99%
“…Differential games in this setting have also been studied, with works such as [15][16][17][18][19][20] considering pursuit-evasion games for systems in infinite-dimensional phase spaces. In certain cases, optimal strategies for players were constructed within appropriate strategy classes.…”
Section: Introductionmentioning
confidence: 99%